Spelling Performance of Portuguese Children: Comparison Between Grade Level, Misspelling Type, and Assessment Task - Magalhães, Sofia; Mesquita, Ana; Filipe, Marisa; Veloso, Andreia; Castro, São Luís; Limpo, Teresa (Frontiers in Psychology, 2020)
There is consensus among researchers that misspellings are something to avoid. However, misspellings also convey relevant information for researchers and educators. The present study is a first effort towards the analysis of misspellings produced by Portuguese children. Specifically, we aimed to examine the association between misspellings in dictation and composing tasks; compare misspellings across grade, type, and task; and test the contribution of different misspellings produced in dictation and in composition to text quality. For that, 933 Portuguese pupils in Grade 2 (n = 297), Grade 4 (n = 302) and Grade 6 (n = 334) performed a spelling-to-dictation task and wrote an opinion essay. Misspellings were categorized into phonetically inaccurate, phonetically accurate, and stress mark errors. Results showed correlations between the same type of misspellings across tasks for phonetically inaccurate errors in Grades 2 and 4, and phonetically accurate errors in Grade 2. Moreover, pupils produced more misspellings in dictation than composing tasks, and there was a progressive decrease in phonetically inaccurate and phonetically accurate misspellings across schooling, though stress mark errors were more frequent in Grade 4 than in other grades. Finally, spelling errors predicted text quality, particularly in younger children. Overall, these findings are aligned with extant results on spelling development and support current voices claiming for fine-grained analyses of misspellings. As they may vary across grade and task, and impact text quality differently, a detailed approach to spelling errors can provide valuable information on the development of this skill.